Genomic variants in the FTO gene are associated with sporadic amyotrophic lateral sclerosis in Greek patients - Konstantinos Mitropoulos; Eleni Merkouri Papadima; Georgia Xiromerisiou; Angeliki Balasopoulou; Kyriaki Charalampidou; Vasiliki Galani; Krystallia-Vassiliki Zafeiri; Efthymios Dardiotis; Styliani Ralli; Georgia Deretzi; Anne John; Kyriaki Kydonopoulou; et al. (Human Genomics, 2017)
Abstract Background Amyotrophic lateral sclerosis (ALS) is a devastating disease whose complex pathology has been associated with a strong genetic component in the context of both familial and sporadic disease. Herein, we adopted a next-generation sequencing approach to Greek patients suffering from sporadic ALS (together with their healthy counterparts) in order to explore further the genetic basis of sporadic ALS (sALS). Results Whole-genome sequencing analysis of Greek sALS patients revealed a positive association between FTO and TBC1D1 gene variants and sALS. Further, linkage disequilibrium analyses were suggestive of a specific disease-associated haplotype for FTO gene variants. Genotyping for these variants was performed in Greek, Sardinian, and Turkish sALS patients. A lack of association between FTO and TBC1D1 variants and sALS in patients of Sardinian and Turkish descent may suggest a founder effect in the Greek population. FTO was found to be highly expressed in motor neurons, while in silico analyses predicted an impact on FTO and TBC1D1 mRNA splicing for the genomic variants in question. Conclusions To our knowledge, this is the first study to present a possible association between FTO gene variants and the genetic etiology of sALS. In addition, the next-generation sequencing-based genomics approach coupled with the two-step validation strategy described herein has the potential to be applied to other types of human complex genetic disorders in order to identify variants of clinical significance.